Barriers to the application of lean construction techniques concerning safety improvement in construction projects. Issue 10 (3rd October 2021) - Enshassi, Adnan; Saleh, Nour; Mohamed, Sherif
Abstract: This paper identifies the barriers that prevent construction projects from implementing LC techniques for safety improvement. To achieve this objective, a deductive approach is adopted using a questionnaire survey of 107 construction professionals. A total of 39 barriers were identified through an intensive literature review, and were grouped into six categories: management, financial, educational, governmental, technical and human attitudinal. Data were analysed using the simple but widely used effect index (EI). The strongest barriers to implementing LC techniques for improving safety in the Gaza Strip are lack of LC concept understanding, lack of government support for applying innovative strategies in construction projects, and lack of knowledge on how to apply LC techniques for safety improvement. Regular training should be provided to all construction practitioners to provide them with the most appropriate LC techniques for improving construction safety. This paper will be valuable for stakeholders in the construction industry to focus their attention and resources on the significant barriers and to identify strategies to address these barriers and facilitate the application of LC techniques to improve safety in local construction projects. It will add value to the existing LC knowledge and to the region.